A dramaturgical theory approach: Symbolic interaction and self-image formation of dangdut singers - YOLANDA, SILVIONA; Wahyono, Eko; Isbandi, Fitri Susiswani; Rohmatunisa, Raden Nita; Ghanistyana, Lathifa Prima; Lestari, Silfiana Dian (Jurnal Studi Komunikasi, 2025)
Dangdut music performances with their dangdut biduan have become an inseparable part of culture and tradition, specifically in Tangerang City, Banten Province, Indonesia. Dangdut music is often present at various events, ranging from celebrations to big events in the city. However, the public's view of this profession still varies; therefore, symbolic interaction is essential in shaping the image of dangdut biduan (singer) so that it can influence public views. The purpose of this study is to understand the role of symbolic interaction in creating the self-image of dangdut both on stage (front stage) and in their roles as housewives (backstage), as well as to determine the response or perception of the community to the formed self-image by dangdut singers from this symbolic interaction by employing a qualitative descriptive research method through a dramaturgy approach. Data collection methods included in-depth interviews, participant observations, and documentation. A triangulation method was used to ensure the validity of the data. Data analysis techniques included data collection, data reduction, data presentation, and conclusions drawn. The results of this study show that symbolic interaction has a central role in forming a positive image for dangdut singers through attractive physical performance, adaptability to the music played, interaction with the audience, and teamwork. The ability to effectively communicate and adapt to others is crucial in providing a special experience on stage. In addition to being a housewife, symbolic interactions also combine commitment, balance, communication, and family support to create a positive and motivating image. The positive response from colleagues, the social environment, and the audience reflects humility and an attitude that is in harmony with the culture of dangdut biduan, so that it is in harmony with the wider community.